Combining Enzymatic and Subcritical Water Treatments for Green Extraction of Polyphenolic Co-pigments from Saffron Tepals - Vardakas, Alexios; Vassilev, Kiril; Nenov, Nenko; Passon, Maike; Shikov, Vasil; Schieber, Andreas; Mihalev, Kiril (Waste and biomass valorization, 2024)
Purpose Two major developments have taken place in the agri-food industry in recent decades. First, valorization of the plant by-products can contribute significantly for ensuring sustainability, especially applying green technologies for recovery of bio- and/or techno-functional compounds. Second, substitution of synthetic food additives, particularly colorants, by their natural counterparts is of utmost importance to meet consumer demands. The aim of this study was to evaluate a new process for green extraction of polyphenols from Crocus sativus tepals, the primary by-product of saffron spice production. Methods A new strategy for recovery of polyphenols from saffron tepals was studied. An extraction process combining two subcritical water extractions steps with enzymatic treatment incorporated between them was established on a pilot scale. Liquid chromatography–mass spectrometry was used for polyphenols profile characterisation. The co-pigmentation efficiency of the polyphenol extract and its effect on thermal stability of strawberry anthocyanins were evaluated in model solutions. Results An approximately fourfold increase in the polyphenolic yield was achieved with the new combined extraction method. 16 flavonoids, mainly flavonols, were detected in the saffron tepal extract. To the best of our knowledge, the presence of the flavone apigenin has not been described before in Crocus sativus . The addition of saffron tepal polyphenols, acting as co-pigments, significantly reduced the thermal degradation of strawberry anthocyanins. Conclusion The obtained results demonstrate an innovative approach for the valorisation of saffron tepals through potential application of the by-product polyphenols in fruit processing. Graphical Abstract